DEVELOPMENT OF LOAD BALANCING MECHANISMS IN SDN DATA PLANE FAT TREE USING MODIFIED DIJKSTRA’S ALGORITHM - Muhammad Fattahilah Rangkuty; Royyana Muslim Ijtihadie; Tohari Ahmad (JUTI: Jurnal Ilmiah Teknologi Informasi, 2020)
SDN is a computer network approach that allows network administrators to manage network services through the abstraction of functionality at a higher level, by separating systems that make decisions about where traffic is sent (control plane), then forwarding traffic to the chosen destination (data plane). SDN can have problems with network congestion, high latency, and decreased throughput due to unbalanced traffic allocation on available links, so a load-balancing load method is needed. This technique divides the entire load evenly on each component of the network on the path or path that connects the data plane and S-D (Source Destination) host. The Least Loaded Path (LLP) of our proposed concept, which is a Dijkstra development, selects the best path by finding the shortest path and the smallest traffic load, the smallest traffic load (minimum cost) obtained from the sum of tx and rx data in the switchport data plane involved in the test, this result which will then be determined as the best path in the load balancing process.